Determinant of Compliance Investors in Satisfying a Fiscal Obligation - Purba, Togi Parulian (International Journal of Economics and Financial Issues, 2017)
Problems which have been elaborated to relate to phenomenon less optimal its make-up of PAD (Original Region Revenue) where tending to because the happening of degradation of trust of investor society at Local Government so that have implication to compliance of investor in fulfilling fiscal obligation of them. The Purpose of this research is to know description concerning accurate variable, and also measure influence of relations public marketing and human resource quality to trust and compliance of investor in executing fiscal obligation of them. The methods of this research are descriptive and explanatory survey. Unit analysis of this research is investor on duty Government of Sub-Province of South Bangka, sample size is 92 Investor. Statistical test to be used by path analysis. The research finding, that is Marketing public relations and quality of HRM have an effect on to trust of investor. Marketing Public relations and quality of HRM simultaneous have an effect on to compliance of investor in fulfilling fiscal obligation of them. Trust of investor have an effect on to compliance of investor in fulfilling fiscal obligation of them. Keywords: Marketing Public Relations, Quality HRM, Trust, fulfilling, investor JEL Classification: G38